Crimes Committed within the Framework of the Institution's Foreign Relations - the crime of abuse of the position of domination- - Benazza, Amal; Himmi, Sidi Mohamed (Future Science, 2025)
This study examines the crime of abuse of a dominant position as one of the most significant anti-competitive practices that undermine market competition. The research aims to analyze the legal framework governing such practices under Law No. 03-03, as amended and supplemented by Law No. 12-08 on competition, and to clarify the mechanisms adopted by the legislator to prevent and sanction this conduct. Relying on a descriptive and analytical methodology, the study reviews the concept of economic dominance, the conditions for establishing abuse, and the forms through which it manifests in the market. It also analyzes the complementary roles of the Competition Council, as an independent administrative authority, and the judiciary in combating these practices through administrative and criminal sanctions. The study concludes that the effectiveness of combating the abuse of a dominant position depends on the integration of administrative and judicial interventions, which together contribute to protecting market integrity, ensuring fair competition, and safeguarding the interests of economic agents.